Plant growth and phosphorus uptake in mycorrhizal rangpur lime seedlings under different levels of phosphorus - Nogueira, Marco Antonio; Cardoso, Elke Jurandy Bran Nogueira (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the response of rangpur lime (Citrus limonia) to arbuscular mycorrhiza (Glomus intraradices), under P levels ranging from low to excessive. Plants were grown in three levels of soluble P (25, 200 and 1,000 mg kg-1), either inoculated with Glomus intraradices or left noninoculated, evaluated at 30, 60, 90, 120 and 150 days after transplanting (DAT). Total dry weight, shoot P concentration and specific P uptake by roots increased in mycorrhizal plants with the doses of 25 and 200 mg kg-1 P at 90 DAT. With 1,000 mg kg-1 P, mycorrhizal plants had a transient growth depression at 90 and 120 DAT, and nonmycorrhizal effects on P uptake at any harvesting period. Root colonization and total external mycelium correlated positively with shoot P concentration and total dry weight at the two lowest P levels. Although the highest P level decreased root colonization, it did not affect total external mycelium to the same extent. As a result, a P availability imbalance affected negatively the mycorrhizal symbiosis and, consequently, the plant growth.